Information and communication technology and the knowledge society - Aseel Hameed Raheem , Nabeel Imran Mussa Al-Khaldi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The subject of research on information and communication technology in building a knowledge society. The general question in this paper may be as follows: What are the impacts of information and communication technology and e-education on building a knowledge society? . The researchers in this research seek to achieve an overall goal of identifying information and communication technology and e-education and its relationship to building the knowledge society. The importance of research is evident that information and communication technology and e-education issues have had and their role in building the knowledge society in recent years. The most important conclusion of the researchers in the knowledge society has recognized the role and right to life of the individual, the freedom to express an opinion, the freedom to choose who represents, the facilitation of trade, and the opening of new markets. The knowledge society recognizes all the rights of the individual to modern knowledge and technology and a fair return on the wealth of the society for specific efforts to the knowledge society and the knowledge economy, the potential for employment, and various basic needs. Also, requirements that support its human development to contribute positively and effectively to its well-being and choice as an individual to the progress of the community to which it belongs to exercise the requirements of the knowledge society.